Oral Cancer: A New Epidemic Can Be Foreseen In Pakistan - Prof. Dr. Pirzada Qasim Raza Siddiqui (ziauddin University, 2024)
Cancer of the oral cavity in Pakistan is among the highest in the world which is attributed to the local custom of chewing tobacco products such as paan, gutka and naswar. These things are widely used in Pakistan mainly by the lower socioeconomic group. They pose a high risk for oral cancer. The continuous exposure to corrosive condiments causes abrasions of oral mucosal surface making it more susceptible for virulent strains to gain entry into the basal cells...